Dynamic De-responsibilization in Business–Government Interactions. Issue 8 (August 2019) - Hamann, Ralph
I contribute to the 'political CSR' debate on whether companies can or should fill public governance gaps by exploring how related business–government interactions may result in corporate social irresponsibility. I studied interactions between mining companies and the government in South Africa between 2002 and 2012, focusing on processes that contributed to the deterioration of living conditions in the Marikana area, site of an infamous massacre in 2012. The analysis resulted in a process model of dynamic de-responsibilization, in which business–government interactions progressively dissipate the adopted and enacted social responsibilities of both the government and business. This extends extant critiques of political CSR and elaborates CSiR as not only a systemic, but also a processual phenomenon, and it focuses related scholarly and practical attention on problematizing the government's role as custodian of democratic accountability.